Investigation of fly ash for sorption of copper ions in multiple contaminant system: An implication on re-use of waste material under concept of sponge city. (August 2018) - Buragohain, Poly; S., Sreedeep; Lin, Peng; Garg, Ankit
Highlights: Retention of heavy metal copper in fly ash under multiple ions. Limitations in analytical solution for predicting retention under multiple ions. Retardation factor from Freundlich isotherm predicts more than Langmuir. Freundlich isotherm is recommended modelling transport of copper ions. Abstract: Many previous studies of soil contaminant treatment have primarily analysed heavy metal contaminant ion retention in fly ash (FA) in a single isolated medium whereas, factoring out the competitive systems. This study seeks to determine the interaction of the heavy metal copper ion (Cu +2 ) with fly ash under single and competitive systems and also to expound its impact on fate prediction. Freundlich and Langmuir non-linear isotherms were adopted to quantify the sorption results. The retardation factor attained from Freundlich isotherm predicts more than Langmuir. The Langmuir isotherm break-through-curves (BTC) was slightly earlier in break through, with a sharp front and prolonged tailing, whereas the Freundlich isotherm appears considerably after the production of a spreading pollutant front. Freundlich retardation factors established in this study was employed to one-dimensional (1-D) solute transport model, which successfully stimulated good prediction for sorption by fly ash. Conversely, significant inconsistencies were identified from the Langmuir isotherm for evaluating the fate of Cu +2 at high concentration range. This study recommends Freundlich isotherm for modelling transport of copper ions in a competitive environment in fly ash.